Годовой абонемент на тот свет - Донцова Даpья Аpкадьевна (Иронический детектив, 2019)
Экземпляры: Ф. 1 (20190702) / Инвентарный номер: 47057 / Цена: 136.00 / Сис.шифр: Р 2 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84 (2Рос=Рус)6-44